Evaluation of aortic stiffness in Gilbert syndrome patients: a protective effect of elevated bilirubin levels - Süleyman Yüce; Erkan Cüre; Yüksel Çiçek; Medine Cumhur Cüre; Arif Yılmaz; Bayram Kızılkaya (KARE Publishing, 2015)
OBJECTIVE: Gilbert's syndrome (GS) is an autosomal recessive disease that is characterized by an increase in indirect bilirubin (IB). The incidence of atherosclerotic heart disease is decreased in GS. This study aimed to investigate the relation between pulse wave velocity (PWV) and the presence of GS. METHODS: The study included 58 GS patients (32 females, age; 27.12+-7.27 years, 26 males, age; 26.63+-5.84 years) admitted to the internal medicine clinic of the hospital. The control group included 58 healthy individuals (35 females [27.33+-8.06 years old, p=0.716] and 23 males [27.38+-6.91 years old, p=0.923]). PWV of both groups was measured from the right carotid and femoral arteries. RESULTS: Mean age of the GS group was 26.03+-8.22 years, while that of the healthy group was 26.60+-5.84 years. The GS group's diastolic blood pressure and PWV were significantly lower than those of the control group: 67.76+-8.59 mmHg vs 71.72+-7.28 mmHg; p=0.008, and 5.63+-1.12 m/s vs 6.18+-1.22 m/s; p=0.014 respectively. The GS group's high density lipoprotein (HDL) level was significantly higher than that of the control group: 1.4+-0.3 mmol/L vs 1.2+-0.3 mmol/L, p=0.029. CONCLUSION: This study found PWV among GS patients to be lower than that among non-smoking and aged-matched healthy controls.